Bewertung und Grammatikalität regionaler Syntax.: Eine empirische Untersuchung zur Rolle der SprecherInnen und HörerInnen - Hanulíková, Adriana (Linguistik Online, 2019)
This paper addresses how morphosyntactic variation stemming from the Alemannic regional variety is perceived, evaluated, and judged in written and spoken language. Based on data from a questionnaire and speeded grammaticality judgments, this study examines which grammatical variants are salient to the listener as a function of speaker accent (regional vs. standard) and listener background (students from different school types and cities). The results show that, in addition to the regional morphosyntax, regional accent co-determines grammaticality judgements, in particular for naive listeners. Expert listener (students of language and literature) judgements are less affected by speaker accent, and appear to follow their subjective normative expectations concerning the prescriptive syntax usage. The most normative judgments on both syntactic and phonological levels were observed for dialectal variants within a group of high school students, despite being active users of the Alemannic variety. This result is a likely consequence of an explicit discard of dialect usage during classroom interactions.